ULTRASTRUCTURE OF THE HINNY (EQUUS-ASINUS X EQUUS-CABALLUS) SEMINIFEROUS EPITHELIUM - Landim-Alvarenga, Fernanda da Cruz [UNESP]; Bortolozzi, J. (Wiley-Blackwell, 1994)
The gonads and the germinative cells of 3 male hinnies were studied with light and transmission electron microscopy with the aim to observe the development of germ cells and verify the morphological modifications due to the hybridization. The hinny seminiferous epithelium presented Sertoli cells and spermatogonia with normal features and anomalous spermatocytes I. The other cells from the spermatogenic sequence were not seen. Most of the alterations began to occur in the cytes I, which presented nuclear vacuolization and deposits of amorphous material between the carioteca and the nuclear lamina, forming vesicles, or exaggerated chromatin condensation, resulting in pyknosis. In the cytoplasm vacuolization was also observed, besides organelle destruction.The arrest of meiosis due to lock of chromosome homologies leads to germinative cell degeneration and, therefore, the spermatogenesis arrest. This fact causes a profound alteration in the seminiferous epithelium morphology in comparison with the parental species.